Repurposing mebendazole to reprogram oncogenic and tumor-suppressor networks: Multi-cancer insights from ENOX2, MMP2, RASSF1A, WFDC10A and METTL7A - Rasha Shaker Aqel; Areej Sami Ismail; Mohamed El-Tanani; Shakta Mani Satyam (PLoS ONE, 2026)
Background Cancer progression involves coordinated regulation of oncogenes and tumor suppressors. This study explores the interplay of ENOX2 (ecto-NADH oxidase disulfide-thiol exchanger 2), MMP2 (matrix metalloproteinase-2), and regulatory genes Ras Association Domain Family Member 1, Isoform A (RASSF1A), WAP Four-Disulfide Core Domain Protein 10A (WFDC10A), and Methyltransferase-Like Protein 7A (METTL7A) across multiple cancer cell lines, and evaluates the anticancer potential of repurposed mebendazole. Methods Eight human cell lines, including breast (MCF7 and MDAMB231), colorectal, pancreatic, lung, hepatocellular, leukemia, and endothelial models, were profiled by qRT-PCR and Western blotting. Expression was assessed under basal conditions and following mebendazole exposure (0.7 µM). Results Basal expression revealed elevated ENOX2 and MMP2 in aggressive cancers (MDA-MB-231, PANC1). Mebendazole significantly downregulated ENOX2 in HEPG2 (p < 0.01) and K562 (p < 0.05), and suppressed MMP2 in MDA-MB-231 (p < 0.05) and MCF7 (p < 0.01), indicating anti-invasive effects. Tumor suppressors were selectively induced: RASSF1A increased >200-fold in endothelial cells (p < 0.01) and was upregulated in HEPG2 and HT29 (p < 0.05), while WFDC10A was strongly elevated in MDA-MB-231 (>40-fold, p < 0.001). METTL7A displayed endothelial enrichment with heterogeneous tumor-specific regulation. Collectively, these findings reveal cell-type–specific modulation of oncogenic and suppressor pathways. Conclusion This multi-cancer investigation identifies ENOX2–MMP2 signaling as a functional driver of invasion and metastasis and demonstrates that mebendazole reprograms oncogenic–tumor suppressor networks. By integrating biomarker profiling with drug repurposing, our study highlights the translational potential of mebendazole as a cost-effective anticancer agent and supports the development of multi-gene biomarkers for diagnosis and therapy in aggressive malignancies.